CHALLENGES AND TRENDS REGARDING THE IMPLEMENTATION OF ICT SOLUTIONS IN THE MANAGEMENT OF CUSTOMER SERVICE DEPARTMENT, WITH CASE STUDY AT AS&ICT ROMANIA - Gurgu, Elena; HRENIUC, Tudor-Vladimir (Annals of Spiru Haret University. Economic Series, 2023)
The motivation for choosing the theme is primarily due to our passion for the ICT field. In this work, we first approached the study and analysis of the national and international ICT market from the last 5 years, then we will refer to the challenges and trends regarding the implementation of ICT solutions in the management of the customer services department, with a case study at the Company AS&ICT Romania[1]. The ICT industry in Romania represents one of the most prosperous economic sectors, registering a turnover of almost 6 billion euros in 2019, representing approximately 5.5% of the country's Gross Domestic Product. In 2020, the IT&C sector had a turnover of 70.3 billion lei and was in the Top 5 economic sectors, along with manufacturing, construction, transport, and storage The purpose of the paper is mainly to follow the evolution of the ICT market on a national and international level in the last 5 years. The objectives pursued in the paper have in mind the establishment of the year-by-year evolution of the national and international ICT market, as well as the impact it generates on the economy and everyday life. The importance of the theme for research and for the business environment consists in the fact that increasingly in recent years the ICT field represents in the business environment an important pillar in the digitization and automation of services. Digitization means a large number of tools that make work more efficient within a company. The novelty of the paper's theme would consist in measuring the impact of the influence of the ICT industry on the perception of everyday life, studying the growth of the national and international ICT industry, as well as its impact on the business environment. [1] In order to protect the identity of the company and the statistical data used in this work, we chose not to disclose the real name of the company where we conducted the case study.